Ancient starch analysis of grinding stones from Kokatha Country, South Australia. (February 2019) - Owen, Timothy; Field, Judith; Luu, Sindy; Kokatha Aboriginal People,; Stephenson, Birgitta; Coster, Adelle C.F.
Abstract: Identifying the range of plants and/or animals processed by pounding and/or grinding stones has been a rapidly developing research area in world prehistory. In Australia, grinding and pounding stones are ubiquitous across the semi-arid and arid zones and the associated tasks have been mostly informed by ethnographic case studies. More recently, plant microfossil studies have provided important insights to the breadth of plants being exploited in a range of contexts and over long time periods. The preservation of starch and/or phytoliths on the used surfaces of these artefacts is well documented, though the factors determining the survival or destruction of use-related starch residues are still largely unknown. Some of these artefacts have also been used for grinding up small animals and these tasks can be identified by specific staining methods for organic remains such as collagen. In this study, 25 grinding and pounding stones identified during an archaeological project in arid South Australia, were examined for starch and collagen residues. The artefacts were from 3 locations in central South Australia, all located in exposed settings. Of these localities, Site 11 in the Western Valley near Woomera is an important Aboriginal landscape specifically associated with male ceremonial practice in the recent past. The remaining two sites, one in the adjacent Nurrungar Valley and the other near Andamooka 100 km distant, have unrestricted access and potentially a different suite of residues. The Kokatha Mula Nations, the Traditional Owners of Woomera, requested that this study be undertaken to explore the range of plants that may have been processed here. It provided an opportunity to investigate the preservation potential of starch and collagen on grinding stones; explore the range of taphonomic factors involved in the persistence of residues in extreme environmental conditions; and test the methodological developments in identifying specific plant origin of starch residues. Of the 25 grinding/pounding stones tested, 7 yielded starch grains. Geometric morphometric analysis identified 3 economic grass species, Crinum flaccidum (Andamooka Lily) and Typha domingensis (Bulrush/Cumbungi). Folded collagen was identified on one artefact. Oral histories recount the movement between Andamooka and Nurrungar/Western Valley for men's ceremonies, and documented in the movement of stone resources, e.g. oolytic chert. The survival of residues in this environment and the identification of economic plant taxa complement the current knowledge of ceremonial activities and the movement of people and resources across significant distances in arid South Australia. Highlights: Survival of starch residues on ground surface artefacts in desert environment Geometric morphometric analysis identified 5 plant taxa Identification of Crinum flaccidum a medicinal plant, subterranean starchy bulb and identification of Typha domingensis /Bulrush, subterranean starchy rhizomes Species correlated to ceremonies for men in exclusive location Indication of long term transport of some species for use during stay in remote valley